Voluntas Symposium: Comments on Salamon and Sokolowski's Re-conceptualization of the Third Sector - Defourny, Jacques; Grønbjerg, Kirsten; Meijs, Lucas; Nyssens, Marthe; Yamauchi, Naoto (Voluntas (Manchester, England), 2016)
With their "Beyond Nonprofits: Re-conceptualizing the Third Sector", Salamon and Sokolowski have made an important contribution to the ongoing debate on how to define the third sector. This Voluntas symposium brings together the comments of five leading scholars both supportive and critical of the new definition. The comments are based on a debate held at the conference of the International Society for Third Sector Research, in Stockholm in 2016.